2014
DOI: 10.1002/ptr.5154
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Black Raspberry on Lipid Profiles and Vascular Endothelial Function in Patients with Metabolic Syndrome

Abstract: Black raspberry (Rubus occidentalis) has been known for its anti-inflammatory and anti-oxidant effects. However, short-term effects of black raspberry on lipid profiles and vascular endothelial function have not been investigated in patients with metabolic syndrome. Patients with metabolic syndrome (n = 77) were prospectively randomized into a group with black raspberry (n = 39, 750 mg/day) and a placebo group (n = 38) during a 12-week follow-up. Lipid profiles, brachial artery flow-mediated dilatation (baFMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 29 publications
7
71
0
Order By: Relevance
“…The latter finding is in alignment with other recent studies pointing to the positive effects of berry consumption on indicators of cardiovascular health, even in patients with metabolic syndrome [37]. Jeong and colleagues recently reported that a BRB extract administered to patients with metabolic syndrome significantly reduced total cholesterol and cytokines including IL-6 and TNF-α levels following 12 weeks of consumption [37]. Obesity is a strong risk factor for both BE and EAC [35, 36]; thus, agents which positively impact risk factors, as well as defined cancer processes hold particular promise.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The latter finding is in alignment with other recent studies pointing to the positive effects of berry consumption on indicators of cardiovascular health, even in patients with metabolic syndrome [37]. Jeong and colleagues recently reported that a BRB extract administered to patients with metabolic syndrome significantly reduced total cholesterol and cytokines including IL-6 and TNF-α levels following 12 weeks of consumption [37]. Obesity is a strong risk factor for both BE and EAC [35, 36]; thus, agents which positively impact risk factors, as well as defined cancer processes hold particular promise.…”
Section: Resultssupporting
confidence: 92%
“…Cholesterol levels reduced from 234 mg/dL at baseline to 226 mg/dL at week 26, following BRB treatment [21]. The latter finding is in alignment with other recent studies pointing to the positive effects of berry consumption on indicators of cardiovascular health, even in patients with metabolic syndrome [37]. Jeong and colleagues recently reported that a BRB extract administered to patients with metabolic syndrome significantly reduced total cholesterol and cytokines including IL-6 and TNF-α levels following 12 weeks of consumption [37].…”
Section: Resultssupporting
confidence: 81%
“…Black raspberry extracts have been shown to be beneficial in adults with the metabolic syndrome, and have been specifically shown to decrease blood glucose and lipids as well as vascular inflammation in pre-diabetic subjects, and also decrease systolic blood pressure in adults with hypertension [32][33][34]. The raspberry doses used in these 8 or 12-week studies were quite high and in most cases not dietary achievable in fresh fruit equivalents.…”
Section: Discussionmentioning
confidence: 96%
“…It also contains significant amounts of tyrosol, resveratrol, tannins, and other phenolic acids [42]. …”
Section: Raspberrymentioning
confidence: 99%
“…Inflammatory markers IL-6 and TNF-α significantly decreased, and anti-inflammatory adiponectin significantly increased, while CRP, ICAM-1 and VCAM-1 were unaffected. Brachial artery flow-mediated dilation significantly improved [42]. …”
Section: Raspberrymentioning
confidence: 99%